Bone marrow-derived vasculogenesis leads to scarless regeneration in deep wounds with periosteal defects - Shirai, Yuuki; Okano, Junko; Nakagawa, Takahiko; Katagi, Miwako; Nakae, Yuki; Arakawa, Atsuhiro; Koshinuma, Shinya; Yamamoto, Gaku; Kojima, Hideto (Scientific reports, 2022)
Deep skin wounds with periosteal defects, frequently caused by traffic accidents or radical dissection, are refractory. Transplant surgery is frequently performed, but patients are subjected to stress for long operation periods, the sacrifice of donor regions, or several complications, such as flap necrosis or intractable ulcers. Even if the defects are covered, a scar composed of fibrous tissue remains in the body, which can cause itching, dysesthesia, or repeated ulcers because of the lack of distribution of peripheral nerves or hair follicles. Thus, treatments with the aim of regenerating lost tissue for deep wounds with periosteal defects are needed. Here, we show that the use of gelatin sponges (GS), which have been used as haemostatic materials in clinical practice, allowed the regeneration of heterogeneous tissues, including periosteum, skin, and skin appendages, when used as scaffolds in deep wounds with periosteal defects in rats. Bone marrow transplantation in rats revealed the mechanism by which the microenvironment provided by GS enabled bone marrow-derived cells (BMDCs) to form a vascular niche, followed by regeneration of the periosteum, skin, or skin appendages such as hair follicles by local cells. Our findings demonstrated that vascular niche formation provided by BMDCs is crucial for heterogeneous tissue regeneration.